Pengalaman Tenaga Kesehatan Dalam Memberikan Layanan Voluntary, Counselling, And Testing (VCT) Pada Masa Dan Pasca Pandemi Covid-19: Studi Kualitatif - Rindiani, Tika; Dewi, Yulia Irvani; Rizka, Yulia (Universitas Pahlawan Tuanku Tambusai, 2024)
Introduction: The Covid-19 pandemic has brought significant changes to healthcare services, including Voluntary Counseling and Testing (VCT). This study aimed to explore the experiences of healthcare workers in providing VCT services during and post COVID-19 pandemic. Methods: This qualitative study with a phenomenological approach involved five healthcare workers at VCT clinics in the working area of Sidomulyo Community Health Center and Lima Puluh District Community Health Center, Pekanbaru City. Data were collected through in-depth interviews and analyzed thematically. Results: There were differences in the implementation of health protocols and VCT service procedures during and post-pandemic. Health protocols were tightened during the pandemic with the addition of PPE and adjustments to service procedures such as the addition of swab tests. The pandemic also impacted the psychological well-being of healthcare workers and patients, causing fear and anxiety. Strategies for promoting VCT services post-pandemic included strengthening internal capacity, reactivating VCT Mobile, disseminating information to schools, and reaching out to key populations. Conclusion: This study provides valuable information about the experiences and adaptations of healthcare workers in providing VCT services during and after the COVID-19 pandemic. Keywords: during Covid-19, health worker experience, pasca Covid-19, VCT